Blood-brain barrier dysfunction and Alzheimer’s disease: associations, pathogenic mechanisms, and therapeutic potential - Chen, Yanting; He, Yanfang; Han, Jinling; Wei, Wenyan; Chen, Feng (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) is a common neurodegenerative disorder characterized by the accumulation of amyloid-beta (Aβ), hyperphosphorylation of tau, and neuroinflammation in the brain. The blood–brain barrier (BBB) limits solutes from circulating blood from entering the brain, which is essential for neuronal functioning. Focusing on BBB function is important for the early detection of AD and in-depth study of AD pathogenic mechanisms. However, the mechanism of BBB alteration in AD is still unclear, which hinders further research on therapeutics that target the BBB to delay the progression of AD. The exact timing of the vascular abnormalities in AD and the complex cause-and-effect relationships remain uncertain. Thus, it is necessary to summarize and emphasize this process. First, in this review, the current evidence for BBB dysfunction in AD is summarized. Then, the interrelationships and pathogenic mechanisms between BBB dysfunction and the risk factors for AD, such as Aβ, tau, neuroinflammation, apolipoprotein E (ApoE) genotype and aging, were analyzed. Finally, we discuss the current status and future directions of therapeutic AD strategies targeting the BBB. We hope that these summaries or reviews will allow readers to better understand the relationship between the BBB and AD.